Redefining Oral African Literature - Omosule, Segun (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
Indigenous art is a peculiar medium. Everything about the human society could be documented, studied, displayed and enjoyed through this. Art, in this sense, encompasses all things that may enhance the human situation. The study examines art and the use to which indigenous people made of it prior to writing using aesthetics as a tool of analysis. The study reveals that art amplifies the glorious, the ennobling as well as the drawbacks from the attainment of lofty goals. Such goals are the ultimate for the evolvement of every society. It is fundamental that art be made a crucial component of human existence if humanity were to evolve, surpass the level of bestiality, and attain a level of decorum that may be germane to peace and progress. It is imperative that indigenous art be studied further in order to unravel the wealth of meaning and possibly the artistic force that might have informed such large scale presence in indigenous societies. Keywords: Oral, Art, Performance, Indigenous, Festivals